Case 3754: Circus assimilis Jardine & Selby, 1828 and Circus approximans Peale, 1848 (Aves, Accipitriformes): conservation of usage by designation of a neotype for Circus assimilis Jardine & Selby, 1828, and suppression of Circus juxta, Peale, 1848 - Debus, Stephen J S; McAllan, Ian A W; Schodde, Richard (Bulletin of Zoological Nomenclature, 2018)
This application has two purposes. The first is to conserve, by neotypification under Articles 75.6 and 81.1 of the Code, usage of the species group name assimilis Jardine & Selby, 1828, universally employed for the Australo-Wallacean spotted harrier in the genus Circus Lacépède, 1799 from the end of the 19th century to the present. As we show here, C. assimilis is threatened because its holotype is identifiable instead with the southwest Pacific swamp harrier, long known as C. approximans Peale, 1848. The second purpose of this application is to conserve, under Articles 81.1 and 81.2.2 of the Code, the species group name approximans Peale, 1848 for the swamp harrier itself. It is threatened by the simultaneously published, but senior by first reviser determination, C. juxta Peale, 1848. No cases have been found of juxta being used as valid since 1956; and usages were few before then. Accordingly, its suppression is requested here because of the great disturbance its uptake would bring to the nomenclature of the widespread and familiar southwest Pacific swamp harrier.
Keywords: Nomenclature; taxonomy; Australia; Aves; Accipitridae; Accipitriformes; Circus approximans; Circus assimilis; Southwest Pacific; spotted harrier; swamp harrier